Apneia obstrutiva do sono e zumbido em adultos - Fonseca, Weidinara de Oliveira Rodrigues da (2022)
Introduction: Obstructive sleep apnea (OSA) can result in changes in sleep architecture, generating negative health consequences by leading to systemic hypoxia. In the long term, it can bring about several physiological damages, such as cardiovascular and auditory symptom alterations. Tinnitus is a symptom present in a large portion of the population with hearing loss, and the perception of it may be closely related to OSA. It is an auditory sensation in the absence of any external sound stimulus, which negatively affects quality of life and interferes with concentration, sleep, social activities and even emotional stability. Objective: The objective of this study is to characterize and observe individuals with OSA and tinnitus. Methodology: This is an observational, non-interventional and prospective study. The search consisted of 38 volunteers diagnosed with obstructive sleep apnea, of both sexes, aged between 27 and 84 years. They underwent an anamnesis regarding sleep and tinnitus complaints, vocal and tonal audiometry and impedancemetry tests, in addition to type 3 polysomnography and the Epworth Sleepiness Scale (ESS). For those with tinnitus, the Tinnitus Handicap Inventory (THI) and the visual analogue scale (VAS) were applied. Results: In the studied sample, there was a greater number of men (52.6%), mean age of 49.33 and Body Mass Index (BMI) of 31.08. In the ESS, there was an above-normal average of 11.3 and 27.89 in the Apnea and Hypopnea Index (AHI), in which 46.2% (n=18) had a severe classification in the AHI. Most patients, about 73.7% (n=28) had hearing loss and 47.4% (n=18) reported tinnitus, most of which were mild on the VAS. It was noticed that individuals with a severe degree of apnea obtained a higher tinnitus rating on the THI (p=0,049) and reported a higher score on the VAS (p=0,048), demonstrating greater tinnitus annoyance. Conclusion: Obstructive sleep apnea is more common in obese men. In addition, we can observe a greater degree of tinnitus annoyance in patients who had severe obstructive apnea, requiring further studies that can relate the two symptoms and corroborate their association for a better tinnitus therapy.